2018
DOI: 10.1080/0284186x.2018.1433320
|View full text |Cite
|
Sign up to set email alerts
|

(ICORG 05-03): prospective randomized non-inferiority phase III trial comparing two radiation schedules in malignant spinal cord compression (not proceeding with surgical decompression); the quality of life analysis

Abstract: Primary radiotherapy for the treatment of MSCC significantly improves QoL in patients not proceeding with surgical decompression. After adjusting for pre-intervention scores, there was no statistically significant difference between a 10 Gy single fraction radiation schedule and one with 20 Gy in five daily fractions on post-treatment QoL Summary scores. For most patients, an effective treatment with low burden would be desirable. A single fraction schedule should be considered for this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…The primary trial objective was to show that ambulatory response rate using a single 8-Gy fraction of radiotherapy was noninferior to a total of 20 Gy of radiotherapy over 5 consecutive days (1 fraction per day) at 8 weeks. Assuming an ambulatory response rate (grade 1 or 2) of 75% of participants in both groups and a noninferiority margin of −11% (defined by consensus among the investigators, approved by the grant funder and the funder’s external reviewers, and similar to or less than noninferiority margins used in other trials), the trial required 386 patients (193 per group) assessable at 8 weeks with 80% power and 1-sided 5% statistical significance. The sample size was inflated to 580 allowing for 33% of participants to die before 8 weeks and later increased to 700 by the independent data monitoring committee because of a higher than anticipated death rate.…”
Section: Methodsmentioning
confidence: 99%
“…The primary trial objective was to show that ambulatory response rate using a single 8-Gy fraction of radiotherapy was noninferior to a total of 20 Gy of radiotherapy over 5 consecutive days (1 fraction per day) at 8 weeks. Assuming an ambulatory response rate (grade 1 or 2) of 75% of participants in both groups and a noninferiority margin of −11% (defined by consensus among the investigators, approved by the grant funder and the funder’s external reviewers, and similar to or less than noninferiority margins used in other trials), the trial required 386 patients (193 per group) assessable at 8 weeks with 80% power and 1-sided 5% statistical significance. The sample size was inflated to 580 allowing for 33% of participants to die before 8 weeks and later increased to 700 by the independent data monitoring committee because of a higher than anticipated death rate.…”
Section: Methodsmentioning
confidence: 99%
“…The ICORG 05-03 phase 3, randomised, multicentre, noninferiority study compared a single dose of 10 Gy and 20 Gy in 5 fractions using a volume including a margin of at least one vertebra above and below the level of compression and dose prescribed to the depth of the cord [45]. Only 112 patients were enrolled and 73 were included in the analysis.…”
Section: Conventional External Beam Radiotherapymentioning
confidence: 99%
“…Until now, three prospective phase III randomized clinical trials compared the effectiveness of SFRT versus MFRT in the treatment of MESCC (16)(17)(18), which demonstrated similarity in functional outcome. In Egypt, Abu-Hegazy et al They found no statistically significant difference in patientreported quality of life or pain scores at five weeks and at three months post treatment.…”
Section: Editorial Commentarymentioning
confidence: 99%